Abundant Fe(III) Oxide‐Bound Arsenic and Depleted Mn Oxides Facilitate Arsenic Enrichment in Groundwater From a Sand‐Gravel Confined Aquifer. Issue 8 (11th August 2022) - Gao, Zhipeng; Guo, Huaming; Qiao, Wen; Ke, Tiantian; Zhu, Zijie; Cao, Yuanyuan; Su, Xiaosi; Wan, Li
Abstract: Enrichment mechanisms of high‐arsenic (>10 μg/L) groundwater in confined aquifers with sand‐gravel sediments were rarely documented. Both groundwater and sediment were sampled to investigate mechanisms of groundwater arsenic mobility in sand‐gravel confined aquifers from the Songnen Basin, China. The results show that, although high arsenic groundwater was present in both shallow sandy (<60 m) and deep sand‐gravel aquifers (60–100 m), relatively higher arsenic groundwater was hosted in the deep confined aquifers. The significantly higher proportion of biologically degradable organic carbon (BDOC) in deep confined groundwater than those in shallow unconfined ones ( p  = 0.03) suggests that higher arsenic concentrations were associated with higher DOM biodegradability. High‐arsenic groundwater was the result of Fe(III) oxide reduction facilitated by BDOC degradation. Arsenic‐rich pyrite framboids were observed in shallow aquifers, which would lower groundwater arsenic concentrations. Sand‐gravel sediments in deep aquifers had remarkably higher contents of extracted Fe(III) oxides and the bound arsenic, HCl‐extractable Fe(II) minerals, and adsorbed arsenic, but considerably lower contents of Mn oxides and Mn(II) minerals than the shallow sandy sediments. Siderite, which is not as efficient as pyrite in sequestering arsenic, was the dominant Fe(II) mineral in the deep aquifer. In the deep aquifer, Mn oxide reduction was almost completed and Fe(III) oxide reduction was predominated, which resulted in high concentrations of groundwater arsenic due to high arsenic/iron molar ratio in the Fe(III) oxides. This study proposed that geogenic high‐arsenic groundwater can occur in sand‐gravel aquifers being high in Fe(III) oxide‐bound arsenic but poor in Mn oxides under reducing conditions. Plain Language Summary: Deep aquifers being mainly composed of sand‐gravel sediments were generally believed to host "safe" drinking water resources. Recently, high arsenic groundwater has frequently been observed in those deep aquifers isolated from shallow groundwater by clay aquitard. However, mechanisms of groundwater arsenic enrichment in those deep aquifers are poorly understood. This comprehensive study shows that arsenic was in situ mobilized from microbially driven reduction of arsenic‐bearing Fe(III) oxides in the deep aquifer with higher proportion of degradable organic carbon to DOC, higher contents of Fe(III) oxide‐bound arsenic and adsorbed arsenic, and lower contents of Mn oxides in the deep aquifer relative to those in the shallow one. The Fe(III) oxide‐bound and adsorbed arsenic were the most reactive mobile phases in deep aquifer sediments with low contents of Mn oxides under reducing environments. Our findings emphasize that the contents of Fe(III) oxide‐bound arsenic and Mn oxides in aquifer sediments were key factors controlling groundwater arsenic enrichment. Key Points: Elevated groundwater arsenic (As) concentration in both shallow sandy and deep sand‐gravel aquifers were caused by Fe(III) oxide reduction Pyrite precipitation lowered shallow groundwater As level, while higher As level occurred in deep aquifers with siderite precipitate High‐As groundwater occurred in sand‐gravel aquifers with high contents of Fe(III)‐oxide bound As and negligible Mn oxides